AB0436 Consolidated long-term safety of infliximab in inflammatory arthritis from a prospective, observational registry. (12th June 2018) - Choquette, D.; Rahman, P.; Chow, A.; Faraawi, R.; Olszynski, W.; Rampakakis, E.; Asin-Milan, O.; Osborne, B.; Lehman, A.J.; Nantel, F.
Abstract : Background: The Bio logic T rial R egistry A cross C anada (BioTRAC) was a multi-centre, prospective, longitudinal, observational program that gathered and analysed data on inflammatory arthritis patients treated with infliximab (IFX), golimumab and ustekinumab. Patients specifically treated with IFX were recruited from July 2002 to June 2015 and followed up to June 2017. Objectives: The objective of this abstract is to document the final consolidated safety data from the BioTRAC IFX cohort. Methods: Treatment was prescribed by the physician per actual clinical practice or standard of care for rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA); there was no randomised assignments to treatment. There were no restrictions on the use of concomitant medications. At enrolment (baseline) and approximately every 6 months thereafter, information was collected to assess safety, clinical outcomes, quality of life, comorbidities, pharmaco-economics and treatment regimens. Results: A total of 1390 patients were enrolled and used for this analysis. The proportion of patients by indication was 59.2% for RA (n=890), 25.9% for AS (n=389) and 7.4% for PsA (n=111). The mean (SD) exposure was 3.10 (3.26) years for a sum of 4290.25 patient-years. Treatment with IFX was generally safe, with AEs and SAEs being reported for 64.3% and 19.5% of patients, respectively. The incidence rate of AEs and SAEs was 116.0 and 11.2 events per 100 pt-years, respectively. More specifically, 338 SAEs were reported by 189 (21.2%) RA patients [SAEs/100 pt-yrs: 11.7], 130 SAEs were reported by 60 (15.4%) AS patients [SAEs/100 pt-yrs: 10.5] and 28 SAEs were reported by 22 (19.8%) PsA patients [SAEs/100 pt-yrs: 8.82]. The most commonly reported AE identified was arthralgia, viral upper respiratory tract infection, upper respiratory tract infection and nausea. For SAEs, the most commonly reported SOC (≥3% of patients) was "Infections and infestations" [5.3% (n=73); 2.16 SAEs/100 pt-yrs] and "Neoplasms benign, malignant and unspecified" [3.5% (n=49); 1.24 SAEs/100 pt-yrs] which occurred at similar rates to the general RA patient population 1 and included two lymphomas [0.1%; 0.05/100 pt-yrs]. Across 3 closely monitored categories of AEs, a total of 302 closely monitored AEs were reported by 293 (21.1%) patients, including cancer (3.7%), lack of efficacy (17.1%) and tuberculosis (0.2%). A total of 21 deaths were reported during the study in 18 RA, 1 AS and 2 PsA patients. Cause of death included MACE (x5), lung cancer (x2), pulmonary fibrosis (x2), pneumonia (x2), respiratory failure, bronchitis, intestinal cancer, throat cancer, intestinal gangrene, disseminated TB, septic shock, procedural complication and drowning. The cause of death was not known for one patient. Conclusions: The results of this longitudinal observational study showed that treatment with IFX was well tolerated in people living with AS, PsA and RA over a 15 year period in a real-world setting. Reference: [1] Askling, et al. Arthritis & Rheum2009;60:3180–9. Disclosure of Interest: D. Choquette Grant/research support from: Janssen Inc., P. Rahman Grant/research support from: Janssen Inc., Consultant for: Janssen Inc., Speakers bureau: Janssen Inc., A. Chow: None declared, R. Faraawi Consultant for: Janssen Inc., Speakers bureau: Janssen Inc., W. Olszynski Consultant for: Janssen Inc., E. Rampakakis: None declared, O. Asin-Milan Employee of: Janssen Inc., B. Osborne Employee of: Janssen Inc., A. Lehman Employee of: Janssen Inc., F. Nantel Shareholder of: Johnson and Johnson, Employee of: Janssen Inc.